92R Monoclonal Antibody Inhibits Human CCR9+ Leukemia Cells Growth in NSG Mice Xenografts - Somovilla-Crespo, Beatriz; Martín Monzón, Maria Teresa; Vela, Maria; Corraliza-Gorjón, Isabel; Santamaria, Silvia; Garcia-Sanz, Jose A.; Kremer, Leonor (Frontiers in Immunology, 2018)
CCR9 is as an interesting target for the treatment of human CCR9+-T cell acute lymphoblastic leukemia, since its expression is limited to immature cells in the thymus, infiltrating leukocytes in the small intestine and a small fraction of mature circulating T lymphocytes. 92R, a new mouse mAb (IgG2a isotype), was raised using the A-isoform of hCCR9 as immunogen. Its initial characterization demonstrates that binds with high affinity to the CCR9 N-terminal domain, competing with the previously described 91R mAb for receptor binding. 92R inhibits human CCR9+ tumor growth in T and B-cell deficient Rag2−/− mice. In vitro assays suggested complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity as possible in vivo mechanisms of action. Unexpectedly, 92R strongly inhibited tumor growth also in a model with compromised NK and complement activities, suggesting that other mechanisms, including phagocytosis or apoptosis, might also be playing a role on 92R-mediated tumor elimination. Taken together, these data contribute to strengthen the hypothesis of the immune system’s opportunistic nature.